Sensory tourism: a case study on Devnar school for the blind/ Pravalhika Vadarevu and Nagarjuna G - Vadarevu, Pravalhika; G, Nagarjuna (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Sensory tourism is a form of tourism aimed at attracting the physical and multi-sensory aspects of travel, enhancing the travel experience specifically for the visually impaired, but also benefits those around it. The visually impaired face many difficulties related to traditional tourism, such as the ability to access information, navigate, safety and knowledge of those around them. This results in visually impaired members traveling much less than non-visually impaired people. This paper aims to determine the challenges and issues faced by visually impaired students and their teachers at Devnar School for the Blind while undertaking and organizing travel respectively, along with identifying facilities and infrastructure required for visually impaired students to undertake travel. The scope of the study focuses on Devnar School for the Blind in Hyderabad, Telangana. The targeted respondents of the research were teachers and students at the school and data were collected through open-ended questions to understand the challenges and issues while undertaking and organizing travel for the visually impaired. The data were analysed with the help of thematic text analysis. The findings from this study will help to determine the issues and challenges and identify scope for improvement in sensory tourism.